Contextual Approach for Expository Essay: A Study of Writing Achievement and Quality - Indrawati, S; Ayob, A (KnE Social Sciences, 2018)
The aim of this study was to investigate the influence of a contextual approach to students’ writing achievement and quality based on some categories (excellent, good, average, and poor). Quantitative and qualitative methods were used in this study. An experimental method was used for the quantitative approach and essay analysis was used for the qualitative one. One hundred and eight of the tenth graders of SMAN 7 Palembang became the sample of the study. The results showed that the writing quality (content, organization, and language) of the students who were taught using a contextual approach was better than that of the students who were taught using an inductive and deductive approach. Students’ writing as being categorized of excellent or good quality was more predominant in classrooms taught using a contextual approach. Keywords: achievement, contextual approach, essay quality